Oblique Cervical Corpectomy in the Management of Unilateral Multilevel Spondylotic Radiculopathy Associated With Myelopathy - Omar Ragab (Egyptian Spine Association, 2017)
Background Data: Oblique cervical corpectomy involves direct decompression of the spinal cord as well as the ipsilateral nerve root but does not require bone fusion or postoperative immobilization. This approach preserves the motion unit anatomically and decreases the risk of adjacent segment disease. Purpose: is to assess the indications, safety, efficacy and complications of oblique cervical corpectomy in the management of unilateral cervical spondylotic radiculopathy associated with myelopathy. Study Design: A prospective clinical case study. Patients and Methods: This study conducted on twelve patients with unilateral cervical spondylotic radiculopathy associated with myelopathy refractory to non-surgical measures for at least 6 months in the period between October 2013 and November 2015. The diagnosis was confirmed by clinical and radiological data. All patients were operated upon at Cairo university hospitals and Al-Haram hospital. Outcome of patients was categorized according to the modified Japanese Orthopaedic Association (mJOA) Scale and the recovery rate was calculated. Results: in this study the average age of presentation was 51 years, the male to female ratio was1:1, and the average duration of symptoms was 11.7 months. Eight cases had right sided radiculopathy and 4 cases had left sided radiculopathy. The most common presenting symptom after brachialgia was neck pain (100%). The most common sign was motor weakness (100%). Most common operated level was C5 and C6 oblique corpectomy. Excellent and good outcomes of patients were obtained in 83.3%. There was statistically significant improvement in the post-operative mJOA score in comparison to the pre-operative. The mean follow up period was 16.5 months with no reported recurrence, instability, progressive kyphosis, vertebral collapse nor other late complications like adjacent segment disease. Conclusion: Oblique corpectomy is a good alternative to conventional median corpectomy and fusion in selected cases for the treatment of unilateral multilevel spondylotic radiculopathy and myelopathy. By avoiding the use of implants and fusion in oblique corpectomy, the procedure is cost effect with no fusion-related complications particularly adjacent segment disease. (2017ESJ130)